THE ROLE OF BOTTOM SEDIMENTS FOR INVESTIGATING HYDROLOGICAL PROCESSES - Bonotto, Daniel Marcos; Ramsey, G.; McHugh, S. (Nova Science Publishers, Inc, 2010)
Sediments are loose earth materials with variable grain size such as sand, silt and clay that accumulate on the land surface, in river and lake beds, and on the ocean floor. They are formed by weathering of different rock types like sedimentary (sandstones, etc.) or crystalline (granites, etc.), and depending on the origin, there are different basic types of sediments: rock fragments (clastic sediments), mineral deposits (chemical sediments) and rock fragments and organic matter (organic sediments). The sediments erode from the site of weathering and are transported by different methods under the influence of gravity, i.e. wind, water, ice, and mass wasting. Bottom sediments occurring in lakes and rivers are often recognized as important sinks for several chemical constituents, mainly metals. The sediments of rivers also contain a repository of valuable historical information on the temporal changes of population growth and industrial development. There is an enormous volume of geochemical work on aquatic systems focusing mainly fluvial, lacustrine and marine bottom sediments or dissolved samples (nominally <0.45 mu m), without equivalent similar studies of the suspended particulate matter (SPM). The paucity of information on SPM has been due in part to the problems of obtaining sufficient amounts of material for analysis, i.e. bottom sediments and dissolved fractions have been most studied as they are abundant and generally easier to sample. However, SPM also plays a significant part in the transport and fate of contaminants such as trace metals, organic compounds and nutrients in aquatic systems. This chapter reports how data obtained for different elements (stable and radioactive) present in bottom sediments and SPM can be utilized to investigate hydrological processes occurring in different hydrographic basins in Brazil, South America. Particular attention is directed for describing the importance of sediments on the adsorption of different stable/radioactive constituents.